Phenomenological structure of mental disorders in combatants - Shuliakova Марія (Psychosomatic Medicine and General Practice, 2026)
Background. Combat veterans represent a high-risk group for the development of stress-related mental disorders, including post-traumatic stress disorder, anxiety, and depressive conditions. The high comorbidity of symptoms contributes to a complex phenomenological structure of mental pathology, necessitating comprehensive investigation. Methods. The study involved 410 combat veterans undergoing medical and psychological rehabilitation in specialized healthcare institutions. Clinical-psychopathological, psychometric, and statistical methods were applied. Mental state assessment included the Spielberger–Khanin Anxiety Scale, GAD-7, PHQ-9, Zung Self-Rating Depression Scale, PCL-5, SAN method (well-being–activity–mood), Schulte tables, and Luria’s “10 words” test. Results. A high prevalence of anxiety (72.7%), depressive (58.8%), post-traumatic (45.4%), and asthenic (52.2%) symptoms was identified. Mean scores were: GAD-7 — 11.9 ± 4.2, PHQ-9 — 12.7 ± 4.5. A decrease in psychofunctional state was observed (SAN: well-being — 3.6 ± 0.9; activity — 3.3 ± 0.8; mood — 3.7 ± 0.7), along with reduced cognitive performance (Schulte tables — 53.2 ± 11.6 s; memory test — 6.1 ± 1.8 words). Significant correlations were found between anxiety and depression (r = 0.64; p < 0.01), as well as negative correlations with psychofunctional state (r = −0.48; p < 0.05). Discussion. The findings indicate the predominance of anxiety-depressive symptomatology combined with post-traumatic manifestations, consistent with current concepts of combat stress psychopathology. Asthenic and cognitive impairments reflect reduced adaptive capacity and may result from prolonged psycho-emotional stress exposure. Conclusions. Mental disorders in combat veterans are characterized by a complex, multidimensional phenomenological structure with dominant anxiety-depressive and post-traumatic syndromes. High symptom comorbidity and the presence of cognitive and asthenic impairments justify the need for a comprehensive approach to diagnosis and rehabilitation. Keywords: mental disorders, mental disorders, combatants,PTSD, depression, anxiety, rehabilitation, psychocorrection